La responsabilité civile du médecin : l’aube d’une crise - Boily, Gratien (Assurances, 1986)
The author takes an in-depth look at the development of general liability for the physician over the last few years, as seen through the eyes of the courts. Mr. Boily speaks of a crisis in the making which, to us, appears to be an accurate perception given the situation of the last few years. However, Mr. Boily does conclude: "By clearly defining the judicial process, we will undoubtedly put a stop to abusive suits. Plantiffs will think twice before taking physicians and hospitals to court".